Relationship between Service Quality and BOR (Bed Occupancy Ratio) Value at Medan Adventist Hospital 2025 - Mendrofa, Wetty Mayanora; Simbolon, Pomarida; Saragih, Pestaria; Ginting, Nasipta (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Background: The creation of service quality will certainly create satisfaction for service users. Service quality is important in health service organizations because it can make the quality of health services efficient. The quality of this service can ultimately provide benefits such as the Bed Occupancy Rate (BOR) value which is very important in assessing the quality of hospital services. Regarding the quality of service carried out using a questionnaire sheet that is categorized as less and good shows the results that the quality of service is in the Good category as many as 21 (60.0%) because patients felt that the service provided by Medan Adventist Hospital was good. The purpose of the study is to identify the Relationship between Service Quality and BOR Value at Medan Adventist Hospital 2025. The sample of this study are 35 respondents with a sampling technique of Quota sampling. The instruments used are questionnaires and Observation sheets. Data analysis with Chi-Square test. The results of this study obtain a good category of service quality for 21 people (60.0%), BOR value above the ideal number of 18 (51.4%). The results of the Chi-Square test obtain a p-value of 0.023 (p <0.05) indicating that there is a relationship between service quality and BOR value at Medan Adventist Hospital in 2025. It is expected that Medan Adventist Hospital will improve the quality of service with BOR value and control and evaluate in order to maintain service quality.